Simulation in paediatrics: An educational revolution - Cheng, Adam (Pulsus Group Inc, 2007)
Recent changes in the culture of medical education have highlighted deficiencies in the traditional apprenticeship model of education, and emphasized the need for more experiential modalities of learning. Simulations, which are scenarios or environments designed to closely approximate real-world situations, have recently found their way into the medical training of health care providers. High-fidelity simulators are life-like mannequins connected to computer systems that control the physiological and physical responses of the mannequin. These simulators are able to provide direct feedback to learners in safe, risk-free environments. This technology has been used to teach all aspects of medical care, including medical knowledge, technical skills, and behavioural training or communication skills. The present article provides a general overview of simulation that will hopefully help to generate interest in paediatric simulation across Canada. Several tertiary care paediatric hospitals in Canada are already using simulation to teach health care providers; continued growth and interest is expected in this exciting area of medical education.